Asian Perspective on Hepatitis B Virus and Hepatitis C Virus Elimination - Apichat Kaewdech; Phunchai Charatcharoenwitthaya; Teerha Piratvisuth (Viruses)
Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections remain significant public health challenges in Asia, affecting millions and contributing to substantial morbidity and mortality. The prevalence of these infections varies across the region, with factors such as vaccination coverage, healthcare infrastructure, and sociocultural barriers influencing the epidemiology of both viruses. The persistent burden of chronic HBV, particularly in older populations, and the evolving HCV genotype landscape highlight the need for targeted, region-specific strategies. Universal screening programs have emerged as essential tools for detecting undiagnosed cases and optimizing healthcare resource allocation. Given the overlapping epidemiology of HBV and HCV, comprehensive public health interventions tailored to the unique contexts of different Asian countries are crucial for achieving global elimination goals. This review examines the epidemiological trends, challenges, and opportunities for addressing HBV and HCV in Asia, emphasizing the importance of overcoming sociocultural barriers to improve prevention, diagnosis, and treatment efforts across diverse populations.